Second European quality of life survesy fieldwork report - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
The Second European Quality of Life Survey was conducted in 31 countries. These consisted of the EU27, the three candidate and acceding countries (Turkey, Croatia and the Former Yugoslav Republic of Macedonia), and also Norway. The target of 1000 interviews was set for most countries, though the larger countries had bigger sample size targets: 1500 interviews in Poland, Italy, France and the UK, and 2000 interviews in Turkey and Germany. The following table (Table 1) shows the target sample size and actual number of completed interviews for each country participating in the survey.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Electronic books